Assessment of Earthquake Behavior of Reinforced Concrete Buildings with Slab Discontinuity - Sağlıyan, Sibel; Yön, Burak (Fırat University, 2018)
The most important principle of the earthquake-resistant design of reinforced concrete structures is that the structural elements must carry both vertical loads and horizontal loads as a whole. For this reason, it is required that the structural elements carry their own weight with sufficient safety and the loads arose from external forces must be transferred safely to the load carrying vertical elements. However, discontinuity of the slabs disturbs the integrity of the structures and causes problems in transferring earthquake loads to the structural elements. In this study, the effect of slab discontinuity in plan on seismic behaviors of multi - storey reinforced concrete structures was investigated by using incremental linear dynamic analysis method. To investigate this irregularity situation, one regular and three irregular multi-storey reinforced concrete building models were selected. Dynamic envelopes of the structures were obtained from the analysis results and compared with each other. Thus, it was observed that the irregular structures subjected to more shear force than the regular structure.
Keywords: Engineering; Mühendislik